Biogeography of Australian Camphorosmeae and Diversification in Climatic Space and Across Arid Habitat Types - Jessica A. Berasategui; Anže Žerdoner Čalasan; Gudrun Kadereit (Ecology and Evolution)
ABSTRACT This study investigates the biogeography of the Australian Camphorosmeae (Amaranthaceae s.l.) lineage and how it relates to shifts in climatic niche and habitat types. Building on previous research and data resources, we integrate molecular phylogenetics, bioclimatic data and biogeographical models to deepen our understanding of the diversification and adaptation of this group across Australia's diverse landscapes in relation to palaeoclimatic changes. For 159 species representing 12 genera, georeferenced distribution points were used to define the most informative bioclimatic variables using principal component analysis. Evolutionary shifts in climatic niches and habitat types were analysed, revealing clade‐specific shifts and adaptations to different habitats and climatic conditions. Biogeographical analyses allowed us to infer ancestral areas of Camphorosmeae in Australia and relate their expansion over evolutionary time to habitat shifts. Preadaptation of this group to warm and dry habitats coupled with key periods of aridification in Australia, particularly during the Late Miocene to Pliocene, were critical in driving its diversification through migration and local adaptation to varied habitats of arid Australia. Our analyses suggest that the ‘Riverine Desert’ habitat offered suitable conditions for ancestral Australian Camphorosmeae and facilitated their early widespread dispersal in the Western and Eastern Desert. We hypothesise that early diverging lineages such as Roycea adapted to the later emerging ‘Desert Lake’ habitat when it spread in Western Australia during the Early Pliocene. Further, habitat type shifts occurred from ‘Riverine Desert’ to ‘Shield Plain’, ‘Karst Plain’ and to ‘Sand Desert’ also during the Pliocene and Pleistocene once these habitat types emerged. This study illustrates the complex interplay between ecological flexibility and niche conservatism in shaping the biodiversity of Australian Camphorosmeae.